Interacting with clients and customers : a foot in the door - Hardman, Lee Sharon, 1954- (Addison Wesley Longman Australia, 1997)
Interacting with Clients and Customers. Interpersonal skills-the basis of communication. Establishing the client relationship. Maintaining the client relationship. Writing the client service policy.